2014
DOI: 10.1111/flan.12065
|View full text |Cite
|
Sign up to set email alerts
|

Study Abroad in Central Spain: The Development of Regional Phonological Features

Abstract: This study investigated the development of two regional pronunciation features by 25 Spanish major or minors from a variety of universities in the United States who studied abroad for one semester in central Spain. Data were collected at the beginning, middle, and end of the semester using three tasks that ranged from reading a formal passage aloud to informal spontaneous speech. All tasks elicited the interdental and the uvular fricative, both salient phonological features of Castilian Spanish. Several lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 23 publications
(41 reference statements)
3
48
2
Order By: Relevance
“…While there is a fundamental shift in the type of study abroad programs popular among college students in the USA, there exists a paucity of research on the outcomes of short-term study abroad programs. Most of the research that has been conducted has explored students' linguistic, sociolinguistic and pragmatic learning outcomes (see George, 2014;Godfrey, Treacy, & Tarone, 2014;Llanes & Muñoz, 2009;Pérez-Vidal & Juan-Garau, 2009;Regan, Howard, & Lemée, 2009;Reynolds-Case, 2013;Warga & Schölmberger, 2007). However, Martinsen (2011) notes 'little research has examined the changes in students' cultural sensitivity through their participation in such programs [short-term study abroad programs]' (p. 1).…”
mentioning
confidence: 99%
“…While there is a fundamental shift in the type of study abroad programs popular among college students in the USA, there exists a paucity of research on the outcomes of short-term study abroad programs. Most of the research that has been conducted has explored students' linguistic, sociolinguistic and pragmatic learning outcomes (see George, 2014;Godfrey, Treacy, & Tarone, 2014;Llanes & Muñoz, 2009;Pérez-Vidal & Juan-Garau, 2009;Regan, Howard, & Lemée, 2009;Reynolds-Case, 2013;Warga & Schölmberger, 2007). However, Martinsen (2011) notes 'little research has examined the changes in students' cultural sensitivity through their participation in such programs [short-term study abroad programs]' (p. 1).…”
mentioning
confidence: 99%
“…Previous research investigating the effect of SA on L2 phonology is relatively limited and has so far produced inconclusive results. The findings of previous research point in several directions, some have found improvement in favor of the SA group (Højen ; Stevens ; Muñoz and Llanes ), others have found differences in favor of the AH group (Mora , ), and still others have found no (clear) differences between SA and AH participants (Díaz‐Campos ; Avello, Mora and Pérez‐Vidal 2012; Avello and Lara ; George ) for a variety of target phonological features such as vowels (Simões ; Mora ; Stevens ), consonants (Stevens ; Díaz‐Campos ; George ), or perceived foreign accent (Avello et al ; Muñoz and Llanes ).…”
Section: The Effects Of Sa On L2 Phonological Acquisitionmentioning
confidence: 98%
“…Concerning the methodology to investigate L2 phonological development in SA, most studies have used foreign accent (FA) ratings as a means of assessing overall improvement in pronunciation accuracy (Avello et al ; Muñoz and Llanes ). In general, research examining specific aspects of phonetic accuracy is less frequent and has focused primarily on segmental production (Stevens , ; Avello and Lara ; George ) rather than on segmental perception (Muñoz and Llanes ).…”
Section: The Effects Of Sa On L2 Phonological Acquisitionmentioning
confidence: 99%
“…The extent to which conclusions can be drawn and compared are limited since the research methods do not ensure that the procedure includes a measure of prior knowledge and maintenance of the features under consideration (George 2014), measuring language contact information abroad (Bongiovanni et al 2015), or learner perceptions of token items (Pope 2016). Müller (2016: 113) reminds her readers that individual learning factors need to be included in the analyses of future studies, which explains why, to date, it has been 'difficult to derive common trends from learner cohorts.…”
Section: Grammatical Competence-phonologicalmentioning
confidence: 99%